The practice of participatory budgeting during the COVID-19 pandemic in Zimbabwe’s local government sector: a case of Chitungwiza Municipality - Mukushwa, Zvimekria Clive; Mapuva, Jephias; Mutema, Edson P. (Brill, 2021)
The experiences of participatory budgeting on the backdrop of the COVID-19 pandemic in Zimbabwe is widely discussed and acknowledged, yet there is paucity of literature of the interface between the two variables. This study therefore seeks to examine how Chitungwiza Municipality has interfaced with Residents and Stakeholders in the participatory budgeting processes during the COVID-19 pandemic. Using informant interviews, non-participant observation, focus group discussions and analytical desk research, the paper argues that COVID-19 pandemic and associated lockdowns has become the most recent threat to the practice of local democracy, particularly to those local government institutions that largely rely more on physical meetings as engaging platforms for participatory budgeting. The study prescribes policy recommendations to improve urban participatory governance within the context of COVID-19 pandemic situation.